Kekuatan Lentur Glued Laminated (Glulam) Kayu Vertikal dan Horizontal dengan Metode ”Transformed Cross Section” The Bending Strength of Vertical and Horizontal Glued Laminated Timber by ”Transformed Cross Section” Method - I. Sulistyawati; N Nugroho; S Surjokusmo; Y S Hadi (Masyarakat Peneliti Kayu Indonesia, 2008)
The bending strength of glued laminated (glulam) timber whose laminas were arranged horizontally will differ from vertically arranged. The important difference was known and used as consideration in lamina arrangement of glulam beam. The determination of precise lamina arrangement will result in maximal strength of design. The aim of this research was to analyze the strength or bending stress in each layer of lamina including maximum stress or modulus of rupture (MOR) of horizontal or vertical glulam beam. The analysis was conducted by using